Waste Segregation through Recycle and Composting Activities in Urban and Suburban Areas. Issue 1 (1st January 2023) - Kasmuri, N; Razak, S N A; Yaacob, Z; Miskon, M F; Ramli, N H; Zaini, N
Abstract: The number of wastes generated in Malaysia is increasing every year. Eighty per cent of solid waste in landfills comes from recycled material, and food waste production has risen to around 15 000 tons per day. Recyclable waste and food waste are the highest waste produced in landfills. Recycling and food composting are two solutions that can reduce waste and slow down the rate of garbage received at the landfill. This research aims to determine the knowledge and awareness of waste segregation through recycling and composting. This paper also identifies the constraint of respondents on performing waste segregation. Here, an online questionnaire has been distributed to the community in urban and suburban areas in Selangor and Johor. A total of 125 respondents participated in this study. Analysis from the survey found no significant difference in the knowledge of waste segregation through recycling and composting between urban and suburban areas. It can be denoted that the respondents have a basic understanding of awareness on waste segregation, although only a few have not practised recycling due to several highlighted constraints. Therefore, some recommendation has been emphasized based on this finding, such as installing reverse vending machines (RVM), organizing campaigns, and providing more information on waste segregation. These suggestions have been the top choices to encourage waste segregation in the community. Moreover, further study needs to be extended to the household group in other states and assessing the effectiveness of RVM will elucidate the segregation behaviours among the community.